1972
DOI: 10.1111/j.1365-2222.1972.tb01303.x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma due to inhaled chemical agents—complex salts of platinum

Abstract: Sixteen workers, from a platinum refinery, with respiratory disease were tested with solutions of complex salts of platinum and ten gave immediate prick test reactions to concentrations of 10"*-10"* and immediate nasal reactions in seven out of eleven tested to concentrations of IO~^-1O'\ Occupational-type exposure inhalation tests to the dust from mixtures of 40 mg of the platinum salt with 1 kg of lactose gave immediate asthmatic reactions in eight and in one of these a late reaction, all also giving immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(37 citation statements)
references
References 10 publications
0
37
0
Order By: Relevance
“…Lung physiological studies of sensitized workers have demonstrated immediate, late, and dual asthmatic reactions, all of which can be inhibited by the inhalation of cromolyn sodium (Lomudal®) before the inhalation provocation test (15). This effect of cromolyn sodium suggests that both the immediate and late reactions are provoked by IgE-mediated mast cell degranulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lung physiological studies of sensitized workers have demonstrated immediate, late, and dual asthmatic reactions, all of which can be inhibited by the inhalation of cromolyn sodium (Lomudal®) before the inhalation provocation test (15). This effect of cromolyn sodium suggests that both the immediate and late reactions are provoked by IgE-mediated mast cell degranulation.…”
Section: Discussionmentioning
confidence: 99%
“…The immunological reaction reviewed can be used for diagnostic purposes (15). It is easy to perform a skin test with platinum chloride or an even more sensitive test with hexachloroplatinate, with either an epicutaneous or a prick test technique (2,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Most often, the suspected agent was mixed in increasing amounts with lactose, which the patient poured back and forth from one tray to another (Figs 1 and 2). This approach was used for piperazine hydrochloride 18 ; wood dusts 19 ; complex salts of platinum 20 ; products of antibiotic manufacturing such as ampicillin, benzyl penicillin, 6-amino penicillin acid and related substances, 21 spiramycin, 22 tetracycline, 23 and intermediate products of sulbutamol 24 ; wheat flour for baker's asthma 25 ; and insect products such as carmine 26 and locusts from a breeding facility. 27 When the occupational exposure resulted from fumes, these were generated for the challenges, as with aminoethyl ethanolamine in aluminum soldering, 28 colophony (pine resin) soldering flux, 29 and electronic soldering 30 ; epoxy resins containing phthalic acid anhydride, trimellitic acid anhydride, and triethylene tetramine 31 ; toluene diisocyanate as a component of varnishes 32 ; and fumes from persulfate salts and henna used in hairdressing.…”
mentioning
confidence: 99%
“…High-molecular-weight agents are mainly proteins that may act as complete antigens and stimulate IgE synthesis. Some low-molecularweight chemicals (<5 kDa), such as acid anhydrides (14), platinum salts (15), and persulfate salts (16), may act as haptens and stimulate IgE production by combining with a protein to form a haptenprotein conjugate.…”
Section: Ige-dependent Mechanismmentioning
confidence: 99%